DNA methyltransferase in the zebrafish Danio rerio: 5-aza-cytidine treatment of embryos in vivo causes disruption in the development of the axial mesoderm. - Martin, C. Cristofre. (University of Ottawa (Canada), 1997)
I have conducted sequence analysis of a zebrafish cDNA that encodes the protein DNA (5-cytosine) methyltransferase. I show that during development transcription of this zebrafish DNA methyltransferase gene is most high at blastula where it is ubiquitously expressed. At 24 hours of development, highest expression is observed in the brain, neural tube, eyes, and differentiating somites. To further assess the role of DNA methylation during development, I treated zebrafish embryos with 5-aza-cytidine (5-azaC), a nucleotide analog known to induce cellular differentiation and DNA hypomethylation in mammalian cell cultures. Treatments with 5-azaC during blastula and early gastrula caused a perturbation of the body axis resulting in loss of tail, and loss or abnormal development of the somites. Histological sections and in situ hybridization revealed whole or partial loss of a differentiated notochord and mid-line muscle in treated embryos. There was loss of expression of no tail in the notochord and eng in muscle-pioneer cells at 24 hours. When examined during gastrulation, 5-azaC treated embryos has a shortened and thickened axial mesoderm. DNA analysis on 5-azaC-treated embryos indicated an overall decrease in DNA methylation when compared to untreated controls. Embryos treated with 6-aza-cytidine, a cytidine analog not known to affect DNA methylation, showed neither abnormal development nor hypomethylation. Our findings suggest that normal DNA methylation is required for proper differentiation of dorsal mesoderm and pattern development of the dorsal-ventral body axis.
Keywords: Biology, Anatomy.